Mapping the Terrain: Examining the Conditions for Alignment Between the Rhetoric of Health and Medicine and the Medical Humanities. Issue 1 (2nd January 2018) - Hannah, Mark A.; Arduser, Lora
ABSTRACT: This article offers an empirical study of literature in the rhetoric of health and medicine (RHM) and the medical humanities (MH). Article traces the topics, funding mechanisms, research methods, theoretical frameworks, evidence types, audience, discourse arrangement patterns, and action orientation that constitute the scholarship in the sample to offer a landscape of the current state of RHM and the MH. Findings can be leveraged to assess the potential for alignment between these fields for future research.